Striving for scientific stringency: a re-analysis of a randomised controlled trial considering first-time mothers' obstetric outcomes in relation to birth position - Thies-Lagergren Li; Kvist Linda J; Christensson Kyllike; Hildingsson Ingegerd (BMC, 2012)
Abstract Background The aim of this study was to compare maternal labour and birth outcomes between women who gave birth on a birth seat or in any other position for vaginal birth and further, to study the relationship between synthetic oxytocin augmentation and maternal blood loss, in a stratified sample. Methods A re-analysis of a randomized controlled trial in Sweden. An on-treatment analysis was used to study obstetrical outcomes for nulliparous women who gave birth on a birth seat (birth seat group) compared to birth in any other position for vaginal birth (control group). Data were collected between November 2006 and July 2009. The outcome measurements included perineal outcome, post partum blood loss, epidural analgesia, synthetic oxytocin augmentation and duration of labour. Results The major findings of this paper were that women giving birth on the birth seat had shorter duration of labour and were significantly less likely to receive synthetic oxytocin for augmentation in the second stage of labour. Significantly more women had an increased blood loss when giving birth on the birth seat, but had no difference in perineal outcomes. Blood loss was increased regardless of birth position if women had been exposed to synthetic oxytocin augmentation during the first stage of labour. Conclusions The results of this analysis imply that women with a straightforward birth process may well benefit from giving birth on a birth seat without risk for any adverse obstetrical outcomes. However it is important to bear in mind that, women who received synthetic oxytocin during the first stage of labour may have an increased risk for greater blood loss when giving birth on a birth seat. Finally it is of vital importance to scrutinize the influence of synthetic oxytocin administered during the first stage of labour on blood loss postpartum, since excessive blood loss is a well-documented cause of maternal mortality worldwide and may cause severe maternal morbidity in high-income countries. Trial registration Unique Protocol ID: NCT01182038 (http://register.clinicaltrials.gov)